1979
DOI: 10.1104/pp.64.5.884
|View full text |Cite
|
Sign up to set email alerts
|

Ribulose Bisphosphate Carboxylase and Proteolytic Activity in Wheat Leaves from Anthesis through Senescence

Abstract: Changes in ribulose bisphosphate carboxylase (RuBPCase) and proteolytic activity were folowed in the flag leaf and second leaf of field-grown winter wheat (cv. Arthur). These changes were foUlowed in relation to changes in leaf chlorophyll, protein, and photosynthesis, and seed development. Levels of RuBPCase were determined by rocket immunoelectrophoresis as described previously (Wittenbach 1978 RuBPCase in the flag leaf and the leaf immediately below it have been followed from full leaf expansion through s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1
1

Year Published

1979
1979
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(68 citation statements)
references
References 15 publications
6
60
1
1
Order By: Relevance
“…Among plant species, inconsistent experimental results have been obtained for the changes in the specific enzyme activity during leaf senescence. It has been reported that the specific activity increased in barley primary leaves (3), declined in wheat leaves (16), and remained constant in rice leaves (7). The changes in the specific enzyme activity in mulberry leaves during their formation and degradation differed somewhat from the results obtained from other plant species.…”
Section: And Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Among plant species, inconsistent experimental results have been obtained for the changes in the specific enzyme activity during leaf senescence. It has been reported that the specific activity increased in barley primary leaves (3), declined in wheat leaves (16), and remained constant in rice leaves (7). The changes in the specific enzyme activity in mulberry leaves during their formation and degradation differed somewhat from the results obtained from other plant species.…”
Section: And Discussioncontrasting
confidence: 50%
“…STODDART and THOMAS (15) noted that nitrogen is removed from aging leaves and redistributed to young expanding leaves according to their requirements. Senescenceassociated degradation of RuBPCase and redistribution of nitrogen within a plant have generally been confirmed in annuals (5,(7)(8)(9)(10)16). In vitro RuBPCase-degrading activity examined in rice leaves, however, did not show a close relation to protein loss during leaf senescence (6).…”
Section: And Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wittenbach (30) and Peoples et al (19) also found that the ratio ofRuP2 carboxylase to soluble protein remained constant until late senescence but then declined. With barley, Friedrich and Huffaker (4) found a relatively constant RuP2 carboxylase specific activity, but found that the ratio of RuP2 carboxylase to soluble protein declined throughout senescence.…”
Section: Resultsmentioning
confidence: 93%
“…The same group has shown that, during the dark-induced senescence of detached leaves of barley, the initial loss of protein is almost entirely due to the degradation of RuBPCase (28). This behavior has also been observed in the dark-induced senescence of attached wheat leaves (37,38). The stability of RuBPCase prior to senescence, and its rapid degradation during senescence, has led to its classification as a leaf storage protein ( 19,21).…”
mentioning
confidence: 83%